Information and communication technology towards job performance among employee at Permodalan Nasional Berhad / Muhammad Qayyum Jamain - Jamain, Muhammad Qayyum (2014)
Information and Communication Technology is very important and it can be said that most the people keep using it from time to time. It can happened with many different ways with the help of equipment such as desktop computer, laptop, notebook, cell phone, telephone, printer, scanner, fax machines, USB drive / Hard drive and Projector. In office setting, employee always being assign with different type of tasks using the software that already being implement within the organization itself. In this research, the researcher is eager to identify the Information and Communication Technology towards job performance among employee in Permodalan Nasional Berhad, Kuala Lumpur. One of the objectives of the research is to determine the type of equipment and application provided by Permodalan Nasional Berhad. The researcher will identify the usage of Information and Communication Technology among the employee Permodalan Nasional Berhad.